2019
DOI: 10.1177/1073191119832657
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Scores From Full Length, Short Form, and Adaptive Tests of the Social Interaction Anxiety and Social Phobia Scales

Abstract: The current study developed and examined the performance of a computerized adaptive version of the Social Interaction Anxiety and Social Phobia Scales (SIAS/SPS) and compared results with a previously developed static short form (SIAS-6/SPS-6) in terms of measurement precision, concordance with the full forms, and sensitivity to treatment. Among an online sample of Australian adults, there were relatively minor differences in the performance of the adaptive tests and static short forms when compared with the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
1
7
0
1
Order By: Relevance
“…The factor models suggested in the article with different cultures were tested and compared, and the results showed that the two-factor model of the short form of the SIAS-6/SPS-6 demonstrated acceptable fit. Consistent with most previous studies (Le Blanc et al, 2014;Erceg-Hurn and McEvoy, 2018;Sunderland et al, 2019;Wong et al, 2019), the SIAS-6/SPS-6 was the most widely used short form in the future and exhibited similar psychometric properties as those of the full forms. This means that the two-factor model is robust and has cross-cultural significance.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The factor models suggested in the article with different cultures were tested and compared, and the results showed that the two-factor model of the short form of the SIAS-6/SPS-6 demonstrated acceptable fit. Consistent with most previous studies (Le Blanc et al, 2014;Erceg-Hurn and McEvoy, 2018;Sunderland et al, 2019;Wong et al, 2019), the SIAS-6/SPS-6 was the most widely used short form in the future and exhibited similar psychometric properties as those of the full forms. This means that the two-factor model is robust and has cross-cultural significance.…”
Section: Discussionsupporting
confidence: 85%
“…Some factor models discussed earlier were tested and compared in the context of Chinese culture. According to previous studies (Carleton et al, 2014;Le Blanc et al, 2014;Gomez, 2016;Mörtberg et al, 2017;Erceg-Hurn and McEvoy, 2018;Sunderland et al, 2019;Wong et al, 2019), we expected the SIAS-6/SPS-6 to fit the data best. Ye et al (2007) employed paper-andpencil full forms to administer the scales, and the Chinese version had better internal consistency and convergent validity.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A bifactor model was used for the confirmatory factor analysis (CFA) (Li et al, 2015 ). Then researchers, via the bifactor function in the psych package of software R4.1.1, conducted a confirmatory factor analysis to test the unidimensionality in the way of high-order bifactor analysis (Gibbons and Hedeker, 1992 ; Reise et al, 2013 ; Sunderland et al, 2020 ). Model fit statistics were used to evaluate model fit and a select optimal number of specific factors and omega.h (ω h ) coefficient.…”
Section: Unidimensionalitymentioning
confidence: 99%
“…Foram elaboradas versões mais curtas dessas escalas -a SIAS-6 e a SPS-6 26 -contando com apenas seis itens cada uma, originalmente no contexto australiano. As versões curtas apresentam resultados bastante satisfatórios em comparação às versões integrais das escalas, apresentando a vantagem de ter um tamanho reduzido, facilitando a aplicação 27 .…”
Section: Introductionunclassified